2016
DOI: 10.15421/011648
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxonomy of vegetation of Kalush hexachlorobenzene toxic waste landfill (Ivano-Frankivsk region)

Abstract: The vegetation of a landfill of hexachlorobenzene toxic waste was studied. It is situated in the neighborhood of Kalush (Ivano-Frankivsk region) and has an area of 4.5 ha. As a result of damage to the containers, hazardous waste has contaminated the air, soil and aquifers at the test site and adjacent areas. During the period 2010–2012 measures were taken to recover and remove the mixture of toxic waste and contaminated soil from the landfill. In its place, unpolluted soil was brought to the landfill. Work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…They act as the main stabilizing element, the ecological framework of the natural environment, minimizing adverse natural processes and phenomena. The anti-flood value of forests is very high under the condition of a normal climatic situation in the region [4][5][6] . Thus, studies [7] in Transcarpathia, where forest cover varies from 12.5% to 96.1%, showed that the modulus of storm runoff of rivers decreases with an increase in the degree of forest cover.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They act as the main stabilizing element, the ecological framework of the natural environment, minimizing adverse natural processes and phenomena. The anti-flood value of forests is very high under the condition of a normal climatic situation in the region [4][5][6] . Thus, studies [7] in Transcarpathia, where forest cover varies from 12.5% to 96.1%, showed that the modulus of storm runoff of rivers decreases with an increase in the degree of forest cover.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal regulation of flood runoff can be traced in watersheds that have 65%-70% of the forest cover [4] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research has focussed on monitoring and identifying the amount of xenobiotic concentration in the soil, water and foodstuffs (Parpan et al, 2016;Febbraio, 2017;Dent & Dmytruk, 2017). The determination of the level of mutagenic danger to organisms of chemical soil contamination within areas of toxic waste warehousing is among the unsolved problems.…”
Section: Introductionmentioning
confidence: 99%